The evolution of malware. Issue 1 (January 2016) - Touchette, Fred
Abstract : After the first personal computers were introduced as kits in 1975, the computing world only had six years before it would be introduced to the very first computer virus, known as Elk Cloner. Computer viruses appeared not long after the introduction of the PC and have become ever more sophisticated and troublesome. Fred Touchette of AppRiver charts the progress of malware and shows how cyber-criminals have constantly innovated. It is not likely that these attacks will go away, but instead they will continue to evolve and will always search for the path of least resistance to get to what they want. Staying informed and up to date on which threats are out there and how they work will help you to fight them.